The Power to (Dis)please: Supernatural Horror and History in Célanire cou-coupé - Livi Yoshioka-Maxwell (Studies in 20th & 21st Century Literature, 2022)
In this essay, I read Maryse Condé’s Célanire cou-coupé (Who Slashed Celanire’s Throat?) as a work of supernatural horror fiction in order to participate in Condé’s reflections on the complexities of interpreting histories of violence. In response to Chris Bongie’s call to re-evaluate Condé’s engagement with popular literature, I contend that popular literacies can be just as useful as more arcane cultural knowledge for interpreting this and other novels by Condé. Previous studies of Condé’s use of popular devices in Célanire cou-coupé approached the novel as an example of the Todorovian fantastique. In positing the eponymous Célanire as a supernatural creature of horror, I set aside the epistemological ambiguity of the fantastique, but this move in fact generates new questions about the meaning of the violent acts attributed to Condé’s protagonist. While Célanire cou-coupé’s horror narrative evokes broader forms of anti-colonial or anti-patriarchal counter-violence, there are limits to an allegorical reading of Célanire’s violence, and, consequently, potential limits to the pleasures typically associated with horror texts.
Keywords: Maryse Condé; Célanire cou-coupé; Who Slashed Celanire& #x27; s Throat; Supernatural horror; Historical fiction; Genre studies; Popular literature; Intertextuality